EVALUATION OF ADVANCED MOLECULAR DIAGNOSTIC TECHNIQUES FOR RAPID DETECTION OF INFECTIOUS DISEASES IN CLINICAL LABORATORY SETTINGS - Talal Hamoud Alshammari, Farraj Hamoud Alshammari, Anoud Jaser Aldhafeeri , Lateefah Sulfeeq Aldhfeeri, Fahed Saleh Alinazi, Tahani Ayed Alinazi , (Chelonian Research Foundation, 2022)
Rapid and accurate diagnosis of infectious diseases is crucial for effective patient management and infection control. Advanced molecular diagnostic techniques have revolutionized the field of clinical microbiology by providing faster and more sensitive methods for pathogen detection. This study aims to evaluate the performance of various molecular diagnostic techniques for the rapid detection of infectious diseases in clinical laboratory settings in Saudi Arabia. The research will focus on the contributions of the authors, who are medical laboratory specialists and technicians, in implementing and assessing these techniques. The study will employ a comparative analysis of different molecular methods, such as real-time PCR, multiplex PCR, and next-generation sequencing, to determine their sensitivity, specificity, and turnaround time. The findings of this study will provide valuable insights into the effectiveness of advanced molecular diagnostic techniques in the context of Saudi Arabian clinical laboratories and their potential impact on patient care and public health.